Historiographical Analysis of Islamic Cultural History Textbook Class X MA 2013 Curriculum - Hidayat, Fahri (Jurnal Tarbiyatuna, 2021)
The emerging polemic about caliphate material in Islamic Cultural History (SKI) curriculum was due to the unfulfilled historiography method in class X SKI textbook. In presenting the material, there was no description or exposition of key terms. Most of the material in class X SKI textbook is written in the form of narration and argumentation. This study aims to analyze problems in SKI textbook material. The method used is analysis of the contents of SKI textbook class X khilafah material. conclusion in this study is that the main problem in class X SKI textbook has not been fulfilled by historiography method in presenting the material. Most of the material is presented in form of narrative and argumentation, but it has not emphasized the description and exposition in each chapter. The main terms contained in class X SKI textbook, namely khulafaur rasyidin, khalifah, hijrah, and futuhat, are only explained in narrative form, but are not spelled out in the form of descriptions and expositions.